Eleven weeks of iron supplementation does not maintain iron status for an entire competitive season in elite female volleyball players: A follow-up study - Mielgo-Ayuso, J.; Zourdos, M. C.; Calleja-Gonzalez, J.; Córdova, A.; Fernandez-Lázaro, D.; Caballero-Garcia, A. (Nutrients, 2018)
Background: Even though iron supplementation can be effective, it is necessary to be cautious of toxicity and aim to do no harm, therefore, it is important to examine the length of time the benefits of iron supplementation can be maintained following its cessation. The main purpose of this study was to analyze if iron stores and strength performance were maintained in elite female volleyball players for the final 18 weeks of a competitive season following the cessation of 11 weeks of iron supplementation. Methods: Twenty-two volleyballers (age: 27.0 ± 5.6 years.) were assigned to two groups (iron treatment group-ITG, n = 11 or control gropu-CG, n = 11) at the beginning of a previous trial (T0) and ITG consumed 325mg/d of ferrous sulphate for 11 weeks (T11). Then, in the present study iron status and strength were measured again 10 (T21) and 18 weeks later (T29) after the cessation of supplementation. Results: At the end of the previous trial (T11), ITG maintained iron status as measured by hematological parameters (serum iron-sFE, serum ferritin-FER, transferrin saturation index-TSI, and hemogloblin-Hb), however, CG showed a decrease in these markers at T11. Further, from T0 to T11 ITG experienced greater (p < 0.05) changes in clean and jerk, power clean, and total mean strength (TMS-sum of all strength tests) than CG. In the present, follow-up investigation, there was a group-by-time interaction in favor of CG vs. ITG from T11 to T21 for FER (p = 0.028) and Hb (p = 0.042). Further, there was an increase for CG (p < 0.001) in power clean for CG from T11 (38.4 ± 1.7 kg) to T21 (41.3 ± 1.9 kg) and T29 (41.8 ± 1.7 kg), but no change for power clean in ITG (p > 0.05). A group-by-time interaction from T11 to T29 occurred in favor of CG for half-squat (p = 0.049) and TMS (p = 0.049). Conclusion: Our findings suggest that the benefits of iron supplementation are not sustained in elite female volleyballers if supplementation is ceased for 18 weeks.